How Commute Time and EV Ownership Shape Residential Cooling Energy Load Profiles - Saquib M. Haroon; Liang Zhang; Alyssa Ryan (Findings)
Commute duration and electric vehicle ownership influence hourly residential cooling demand through their effects on household occupancy patterns. Using data from 10,000 U.S. households, travel behavior was linked to building energy simulation through a co-simulation framework focused on Tucson, AZ, USA. Long commutes were associated with higher peak-to-valley load ratios, while electric vehicle households showed flatter demand profiles with increased early morning and evening loads.